2014
DOI: 10.1364/jocn.6.000371
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Laser and Detector Placement in Incoherent MIMO Multimode Fiber Systems

Abstract: Abstract-Conventional large-core multimode fibers (MMFs) are preferred for use in short to medium haul optical fiber links, owing to their tolerance to misalignment and low deployment costs; however, data rates through MMFs are limited by modal dispersion. Digital signal processing with multiple-input multiple-output (MIMO) techniques has offered promising solutions to overcome the dispersion limitations of MMFs, but the impact of the geometry of laser and detector arrays on the achievable data rate is not est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We avoid this cost by using a suboptimal greedy selection to find the subset of modes for decoding for each channel realization. This yields a subset whose data rate is guaranteed to be within (1 − 1/e) of the the capacity obtained with the optimal subset [19]. In practice, the performance is much better, as can be observed in Fig.…”
Section: B Complexity Reductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We avoid this cost by using a suboptimal greedy selection to find the subset of modes for decoding for each channel realization. This yields a subset whose data rate is guaranteed to be within (1 − 1/e) of the the capacity obtained with the optimal subset [19]. In practice, the performance is much better, as can be observed in Fig.…”
Section: B Complexity Reductionmentioning
confidence: 79%
“…In [19], simulations based on channel models revealed that a significant enhancement in channel capacity could be obtained if laser and detector geometries were designed in accordance with the channel statistics of the fiber. As an example, Fig.…”
Section: A Dsp Motivated Designmentioning
confidence: 99%
“…Such an approach, while suboptimal, reduces the number of comparisons required to O(DL), which is much smaller. Moreover, due to the sub-modularity of the capacity of fiber channels with respect to mode subsets [16], the data rate achieved using greedy mode subset selection is guaranteed to be at least (1 − 1/e) times that obtainable with the optimal subset selection approach [17]. Thus, the rate obtained using suboptimal greedy selection is mathematically guaranteed to be close to that obtained using optimal selection.…”
Section: Sub-modularity and Mode Selection At The Receivermentioning
confidence: 95%
“…from 277 to 665 ps/km for D = 6 to 110. For minimizing the computational complexity, the FFT block length N is optimized based on the criterion described in the previous section, and is found to be to 2 16 . In each of the cases, we generate several channels using the model described in Section II-C, and compare the rate achievable using subset selection for various subset sizes with the capacity obtained using all fiber modes.…”
Section: E Equalizer Complexitymentioning
confidence: 99%